Investigation and Comparison of Medicine Use in the three Central Referral Hospitals in Sierra Leone (Nigerian Journal of Pharmaceutical Research, 2021)
Background: An important goal of National Medicines Policy is to ensure that sufficient quantities of essential medicines are available to health care providers and affordable to patients.Objectives: To investigate and compare the prescribing indicators, patient care indicators and facility indicators in three central referral Hospitals in Sierra Leone.Methods: This was a simple randomized retrospective and prospective study. Three groups were obtained to assess prescribing, patient care and facility indicators in the study sites. About 10% of the prescriptions encountered from January to June 2019, were observed retrospectively. Direct observation of 30 randomly selected patients in each hospital was used to assess patient care.  Data collected were organized using Microsoft Excel and analyzed using SPSS version 21. Ethical considerations were observed.Results:  The average number of medicines prescribed in the three teaching hospitals (Connaught, PCMH and ODCH) were 4.07, 4.3and 3.3 respectively. Percentage encounter with injections were within standard in PCMT and ODCH. Antibiotics prescribing was slightly higher that WHO recommendation of 30% in all 3 hospitals. Percentage of medicines prescribed by generics were 75.4%, 53% and 77% respectively. The average consultation time was 5.47 minutes while the average dispensing time was 79.7 seconds. Patients that receive their medications at Connaught Hospitals had very little knowledge on how they should take their medicine(s), compared to PCMH and ODCH.Conclusion: This study has shown that irrational use of medicines is a major problem in the three referral hospitals occurring majorly during the prescribing and dispensing processes